2020
DOI: 10.4314/acsj.v28i4.1
|View full text |Cite
|
Sign up to set email alerts
|

Performance of dual-purpose pearl millet genotypes in West Africa: Importance of morphology and phenology

Abstract: Pearl millet (Pennisetum glaucum (L.) R. Br.) is a cereal crop vital for food security in West and Central Africa. Its byproducts also serve as fodder for livestock, especially during dry seasons. The objective of this study was to evaluate selected genotypes from West African pearl millet breeding programmes, for dual-purpose (grain and fodder) and elucidate prospects for future breeding. A total of 83 open-pollinated varieties (OPVs), five composites, six landraces, one synthetic and five hybrids were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Kanfany et al (2018) reported an average grain of 1268 kg ha −1 for Souna 3 (TV variety) and 1694 kg ha −1 Thialack 2 (DP variety) in Senegal. In a T A B L E 2 (Continued) multi-site-year trial, Serba et al (2020) showed that DP grain yield averaged 1900 kg ha −1 and 4600 kg ha −1 fodder. Dual-purpose millet varieties can be grown as a rainy season crop under rainfed conditions in SSA, in monocropping or intercropped or mixed cropping systems but also in rotation with legumes such as pigeon pea (Cajanus cajan), groundnut, cowpea, mung bean (Vigna radiata), mucuna (Mucuna sp.…”
Section: Dual-purpose Milletmentioning
confidence: 99%
“…Kanfany et al (2018) reported an average grain of 1268 kg ha −1 for Souna 3 (TV variety) and 1694 kg ha −1 Thialack 2 (DP variety) in Senegal. In a T A B L E 2 (Continued) multi-site-year trial, Serba et al (2020) showed that DP grain yield averaged 1900 kg ha −1 and 4600 kg ha −1 fodder. Dual-purpose millet varieties can be grown as a rainy season crop under rainfed conditions in SSA, in monocropping or intercropped or mixed cropping systems but also in rotation with legumes such as pigeon pea (Cajanus cajan), groundnut, cowpea, mung bean (Vigna radiata), mucuna (Mucuna sp.…”
Section: Dual-purpose Milletmentioning
confidence: 99%